Xylazine awareness and attitudes among people who use drugs in Ohio, 2023-2024 - Nichole L. Michaels; Saroj Bista; Ashley Short Mejia; Hannah Hays; Gary A. Smith (BMC, 2024)
Abstract Background The prevalence of xylazine, a non-opioid tranquilizer not for human consumption, in illicitly manufactured fentanyl is increasing in the United States. However, little is known about xylazine awareness and attitudes among people who use drugs. Methods A cross-sectional survey of people who use drugs in Ohio was conducted from November 2023 - May 2024 to identify xylazine awareness and attitudes in rural and urban counties across the state. Study participants were recruited from naloxone distribution sites, including health departments, syringe service programs, and community-based organizations. Results Among 630 people who use drugs in Ohio, more than one-half (53.5%) were unaware of xylazine being in "street drugs," regardless of urbanicity. Among individuals who were aware of xylazine, most (73.0%) indicated they did not want to use the drug and try to avoid it. In addition, 75.8% of this group felt it was "very" or "extremely" important to know if xylazine was in their drugs. Discussion This research found that many people who use drugs in Ohio are unaware of xylazine and its risks. An important finding of this study is that most individuals who had heard of xylazine did not want to use it and were concerned about knowing whether xylazine was in their drugs.